Skewness as a test of the equivalence principle - Amendola, Luca; Quercellini, Claudia (Arxiv, 2004)
The skewness of the large scale distribution of matter has long been known to be a probe of gravitational clustering. Here we show that the skewness is also a probe of violation of the equivalence principle between dark matter and baryons. The predicted level of violation can be tested with the forecoming data from the Sloan Digital Sky Survey.
Gesehen am 17.11.2017